Transcription level differences in Taxus wallichiana var. mairei elicited by Ce3+, Ce4+ and methyl jasmonate - Han, Na; Geng, Wen-ji; Li, Jian; Liu, Shu-ting; Zhang, Jie; Wen, Yi-jie; Xu, Huai-hua; Li, Meng-yuan; Li, Yan-ru; Han, Pei-pei (Frontiers in Plant Science, 2022)
Taxol is a precious and effective anticancer drug. Cerium and methyl jasmonate (MJ) have been shown to increase the yield of taxol in taxus cells. However, the mechanisms of cerium-mediated and MJ-mediated taxol biosynthesis remain unknown. RNA-Seq was applied to study the overall regulation mechanism of cerium and MJ on taxol biosynthesis and analyze the differences among T. mairei cells elicited by Ce3+, Ce4+ and MJ on transcriptional level. Using sequence homology, 179 unigenes were identified as taxol synthesis genes. Under the condition of 100 μM MJ, taxol synthesis genes were up-regulated. Notably, taxol synthesis genes were down-regulated expression at 1 mM Ce3+ and 1 mM Ce4+. Differential expression genes involved in some related functions were analyzed, such as MAPK signaling pathway and plant-pathogen interaction. Sequence alignment and phylogenetic analysis of nine differentially expressed WRKYs in our data were carried out.